Babesia microti (Piroplasmida: Babesiidae) in nymphal Ixodes ricinus (Acari: Ixodidae) in the Czech Republic - Rudolf, Ivo; Golovchenko, Maryna; Sikutová, Silvie; Rudenko, Nataliia; Grubhoffer, Libor; Hubálek, Zdenek (Folia parasitologica, 2005)
A total of 350 nymphs of the common tick Ixodes ricinus (Linnaeus, 1758) were collected in an endemic focus of Lyme borreliosis (South Moravia, Czech Republic) and examined for the presence of the protozoan Babesia microti (França, 1909) by polymerase chain reaction (PCR), using primers specific for the B. microti gene encoding small subunit rRNA. The assay revealed five positive pools (out of 70 pools examined); the corresponding prevalence rate was about 1.5%. Sequence analysis of the PCR products confirmed their 100% homology with that of B. microti. The study represents the first evidence of B. microti in ixodid ticks in the Czech Republic.
Keywords: Babesia microti; Polymerase Chain Reaction; Nymph; Sequence Analysis, DNA; Ixodes; sekvenční analýza DNA; Prevalence; nymfa; klíště; RNA ribozomální; Animals; Česká republika; Czech Republic; zvířata; RNA, Ribosomal; polymerázová řetězová reakce; prevalence